POLA AKAD DALAM PEMBERDAYAAN EKONOMI MASYARAKAT PERANTAU ATAR - Maisarah Leli; Farida Arianti (JURIS (Jurnal Ilmiah Syariah), 2019)
This paper discusses about the pattern of contracts in the economic empowerment of the Atar migrant community. Many migrants are not easy to get a job that later nomads can be independent. They are looking for work to other areas to be able to get a decent job that will provide their lives. In this section, the writer takes a qualitative descriptive approach by describing the contract pattern in empowerment carried out by the nomads, while the technique is snowball sampling in interviewing the main character until the information obtained at the saturated level, no more new information becomes data in this paper. The results achieved were that the nomads patterned contracts that were used in empowering the nomads community with qiradh contracts, and grants.